2023
DOI: 10.1002/bies.202300088
|View full text |Cite
|
Sign up to set email alerts
|

Defining bone fide effectors of RAS GTPases

Abstract: RAS GTPases play essential roles in normal development and are direct drivers of human cancers. Three decades of study have failed to wholly characterize pathways stimulated by activated RAS, driven by engagement with ‘effector’ proteins that have RAS binding domains (RBDs). Bone fide effectors must bind directly to RAS GTPases in a nucleotide‐dependent manner, and this interaction must impart a clear change in effector activity. Despite this, for most proteins currently deemed effectors there is little mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 165 publications
0
2
0
Order By: Relevance
“…ASPP2 contains an RBD, interacts with oncogenic H-Ras and is a pan-Ras nanocluster scaffold that can neutralize Gal1 nanoclustering and can switch from a Gal1 promoted growth to a senescence phenotype 43 45 . Like the other RBD-containing proteins it was pulled down by L5UR-SNAP, as were its two RA-domain containing interaction partners, RASSF7 and RASSF9, which do not directly bind to Ras 5 , 46 . Quantification confirmed that the mutL5UR-SNAP was ≤50% more efficient than L5UR-SNAP in pulling down any of these proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ASPP2 contains an RBD, interacts with oncogenic H-Ras and is a pan-Ras nanocluster scaffold that can neutralize Gal1 nanoclustering and can switch from a Gal1 promoted growth to a senescence phenotype 43 45 . Like the other RBD-containing proteins it was pulled down by L5UR-SNAP, as were its two RA-domain containing interaction partners, RASSF7 and RASSF9, which do not directly bind to Ras 5 , 46 . Quantification confirmed that the mutL5UR-SNAP was ≤50% more efficient than L5UR-SNAP in pulling down any of these proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The two switch regions of GTP-Ras undergo significant conformational changes upon activation, thus enabling binding to the Ras binding domain (RBD) or Ras association (RA) domain of effectors, such as Raf, PI3Kα, and RASSF proteins. These effectors are implicated in cell proliferation, growth, and apoptosis, respectively 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%